KETERKAITAN AKTIVITAS PRADAKSINA PADA RAGAM TIPOLOGI BANGUNAN STUPA - FERLINA SUGATA (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Circumambulation as one of the Buddhist worship activity is a pathway around the shrines clockwise, from East to the West. There are two kinds of pradaksina activity refer to schools in Buddhism, the Theravada as an honor symbol and the Mahayana as one type of meditation. Stupa as one of Buddhist worship architecture is a place to accommodate the activity itself and the worship symbol as well. Stupa is a conical monument erected over relics of the Buddhas, Arhats, Kings or other great men. Stupa as a religious architecture nowadays became the image of The Buddha as known all around the world which is also known as the symbol of the composition of robe, bowl, and walking stick from a monk. The interrelatedness between the pradaksina as an activity and the stupa as the architecture cause some effects that related to space dimension, space quality, orientation of space, and function of the building. All the effects only influence the spatial matter but not influence the meaning of pradaksina and the stupa. Keyword: pradaksina; stupa’s typology, the interrelatedness